Creatividad y Pensamiento Crítico en la Educación Peruana: una Lectura Inicial desde el Currículo y las Evaluaciones Internacionales PISA 2022 - Vivanco Enríquez, Jesús (2026)
This article analyzes the critical dissonance between curricular discourse andassessment systems in Peruvian secondary education. Through a documentarymethodological approach, complemented by quantitative data analysis, the postulates ofthe National Curriculum for Basic Education (2016) —which promotes creativity andcritical thinking as central axes— are contrasted with the results obtained by Peru in PISA2022. The findings reveal a substantial gap between the innovative rhetoric of thecurriculum and its effective implementation in classrooms, hindered by rigid pedagogicalstructures, traditional methodologies, and an assessment system that prioritizes themeasurement of content over the development of complex competencies. The poorresults in the areas of problem-solving and reflective thinking in PISA reinforce thisdisconnect. It is argued that the genuine development of creativity and critical thinkingrequires specific pedagogical conditions, such as the integration of formativeassessments and inquiry-based learning. The study concludes by emphasizing the needto move towards a more inclusive and dialogical educational model, and by promotingfuture research that explores how Peruvian teachers negotiate these tensions in diversecontexts.